Manifestaciones orales de la infección por COVID-19 entre comunidad de la Universidad Antonio Nariño (2022)
In 2019, a new virus called SARS-CoV2 with a high affinity for the human ACE-2 receptor spread widely in the oral cavity and emerged, infecting nearly 605 million people worldwide. Signs and symptoms related to the oral cavity include dysgeusia, necrotic oral ulcers, and aphthous ulcers involving areas such as the tongue, lips, palate, and oropharynx; however, the prevalence and etiology of these symptoms remain unknown. Objective: The purpose of this research is to describe oral signs and symptoms and their frequency during and after COVID-19 infection